2023
DOI: 10.1155/2023/3524611
|View full text |Cite|
|
Sign up to set email alerts
|

Composite Dietary Antioxidant Index and Plasma Levels of Soluble Klotho: Insights from NHANES

Abstract: Objectives. The association between dietary antioxidants and soluble Klotho (S-Klotho) levels remains unknown. We investigated to explore whether the composite dietary antioxidant index (CDAI) was associated with serum levels of S-Klotho in the middle-aged population. Methods. Eligible participants were identified from the National Health and Nutrition Examination Surveys (NHANES) from 2007 until 2016. The CDAI was calculated from the intake of six dietary antioxidants. The serum levels of S-Klotho were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Proper intake of antioxidants through food could keep our immune system in an optimal antioxidant state ( 23 ). In line with this, a recent study by He et al suggested that high plasma antioxidant level might protect people against age-related diseases ( 24 ). Furthermore, growing research studies demonstrate that oxidative stress is closely related to cardiovascular disease and that total dietary antioxidant capacity (TDAC) is negatively associated with markers of inflammation such as C-reactive protein (CRP), platelet-activating factor (PAF), and adiponectin concentration ( 25–27 ).…”
Section: Discussionmentioning
confidence: 67%
“…Proper intake of antioxidants through food could keep our immune system in an optimal antioxidant state ( 23 ). In line with this, a recent study by He et al suggested that high plasma antioxidant level might protect people against age-related diseases ( 24 ). Furthermore, growing research studies demonstrate that oxidative stress is closely related to cardiovascular disease and that total dietary antioxidant capacity (TDAC) is negatively associated with markers of inflammation such as C-reactive protein (CRP), platelet-activating factor (PAF), and adiponectin concentration ( 25–27 ).…”
Section: Discussionmentioning
confidence: 67%
“…These results are consistent with those of previous studies. 6,8 Although the specific reasons for this finding are unclear, it may be because these individuals have higher levels of oxidative stress, and exogenous antioxidant intake appears to be more protective in those with higher innate or acquired ROS-levels. 34 Our results suggest that people at high risk of CKD may benefit more from overall dietary antioxidant intake.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies reported that a high CDAI is associated with a reduced risk of various types of cancer and diabetes and positively correlated with the plasma levels of S-Klotho, an anti-aging indicator. [4][5][6][7][8] A high CDAI is associated with a decreased risk of all-cause and cardiovascular mortality. 5 Oxidative stress is correlated with renal damage; however, the relationship between the inflammatory indicator CDAI and CKD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a previous study reported that Klotho contributes to the protection of the heart from ischemia/reperfusion injury and oxidative stress by inhibiting the IGF1R/PI3K/AKT pathway may be considered as a novel cardiopreventive/cardioprotective agent 9 . In addition, a positive correlation between composite dietary antioxidant index and Klotho levels in the middle-aged population has been demonstrated 10 . However, oxidative stress levels in the body may be in uenced by various dietary components, physical activity, obesity, smoking and other behaviors 11 .…”
Section: Introductionmentioning
confidence: 98%